Análisis comparativo de los paradigmas de simulación - Sarmiento Vásquez, Alfonso Tullio (2016)
This research work makes a qualitative and quantitative analysis of the simulation paradigms. The three paradigms studied in this work are: system dynamics, discrete event simulation and agent-based simulation. In the qualitative analysis, the definitions and characteristics of each of the three methods are detailed first and then the distinctive elements of each paradigm are showed in a comparative table. The quantitative analysis is performed through a case study, where first the problem is modeled and simulated through the focus of each particular method. After that, by using different scenarios it is showed the advantages and disadvantages of using a paradigm over the others. This is showed in a comparative summary of the scenarios. The integration of the qualitative and quantitative characteristics that distinguish each paradigm are presented in the conclusions.